Developmental, morphological and molecular variation of commercial Ganoderma spp. accessions from southern Vietnam - Viet The Ho; Thi Ngoc Ha Vo; Ngoc Giau Le (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ho VT, Vo TNH, Le NG. 2019. Developmental, morphological and molecular variation of commercial Ganoderma spp. accessions from southern Vietnam. Biodiversitas 20: 3684-3689. In Vietnam, the market value of Ganoderma spp. increases markedly recently due to the high demand as an effective medicine. However, the breeding programs for this mushroom are still less effective due to the poor knowledge of genetic composition. This study was conducted to investigate the diversity of some commercial Ganoderma spp. accessions from southern Vietnam using both traditional techniques using developmental and morphological characterization, and molecular method using ISSR markers. A total of nine Ganoderma spp. samples were collected from production areas and research institutes in southern provinces of Vietnam and targeted for developmental and molecular characterization. Developmental and morphological variations among accessions were evaluation. In addition, 20 ISSR markers were also utilized for further understanding genetic composition of these mushrooms. The obtained measurement data show a large variation among the studied Ganoderma spp. accessions in term of mycelia growth, diameter, shape, and dried weight of fruiting bodies. Molecular data from 20 ISSR markers also supported genetic variation of the examined samples. Based on the results of this study, the samples of Ganoderma spp. accessions from southern Vietnam can be divided into two main groups which are not correlated to geographical locations of sample collection sites. The results are potential for classification and provide new insights for molecular assisted selection of Ganoderma spp.